Appropriating virtual learning environments: A study of teacher tactics. (June 2017) - Derboven, Jan; Geerts, David; De Grooff, Dirk
Abstract: In research on Virtual Learning Environments (VLEs), it has been shown that teachers often do not explore VLEs to their full potential and only adopt a limited set of the available tools. In this article, we approach teachers' design of VLE learning activities as end user development. We describe a study of Toledo, a virtual learning environment used across several higher education institutions in Belgium. Using a combination of a semiotic, multimodal analysis and an in-depth user study with 24 respondents, we provide a detailed account of how teachers appropriate the learning environment to suit their needs. Combining the insights from the semiotic investigation and the user research, we analyze how user appropriations can be explained as practices emerging from both how the platform communicates, and contextual factors. The study showed that some teachers design very specific learning activities using the VLE - not by using the dedicated VLE tool, but by reinterpreting more generic tools. These appropriation tactics concentrate platform use in a limited number of tools, even when teachers do use more complex learning activities. These results have implications for the design of VLEs: rather than offering a wide range of tools targeted at specific learning activities, VLEs could concentrate on providing basic communication tools that are open for appropriation. Highlights: We investigate teachers' appropriation of a virtual learning environment. We combine multimodality and ethnographic methods to investigate appropriation. We use the concept of meaning potential to explore shifts in technology meaning. Teachers appropriate generic communication tools instead of using dedicated tools.